The impact of the new technologies on managing projects funded by Interreg Central Europe with migrants as the external stakeholders during the COVID-19 pandemic - Anna Drabina; Sylwia Krzyżek-Liburska; Katarzyna Wójcik (Trends Economics and Management, 2021)
Purpose of the article: The objective of this research was to examine the helpfulness of new IT tools which are used to project management. IT tools have been an important part of project management for a long time but after the pandemic time became an absolute necessity. The authors of this research examined whether project managers dealing with big international projects based on soft skills with the necessity of quick communication with internal and external stakeholders are convinced to work with a new tool and find it helpful. Methodology/methods: As a research sample, four consortiums of Interreg Central Europe have been chosen. Each consortium consists of 10 to 12 participant institutions, including the institutions of higher educations, NGOs and municipalities. The main objective of all selected projects is to support groups of migrants and refugees from programme countries. For the purpose of the research, the survey was designed and submitted to all institutions and project managers involved in four chosen projects. Scientific aim: The aim of the paper was to identify the issues regarding project management and risk management before and during the COVID-19 pandemic within Interreg Central Europe programmes considering internal and external stakeholders of the four chosen projects. Findings: The study showed that owing to the use of new IT tools, it was possible to maintain and improve communication in international project teams during the pandemic. The study also showed that surveyed project managers find helpful to work with new IT tools; however, they recognize risks related to communication with external project stakeholders. Most of those surveyed stated that new IT tool boosted the project teams' communication but did not affect communication with digitally excluded stakeholders. Conclusions: In the authors' opinion, the results confirm the purposefulness of using and developing the new IT tools despite issues with reaching external stakeholders. In the next step, the research will focus more on the external stakeholders' issues with access to digital technologies, especially IT tools themselves.
Keywords: M15; M21; 650; project management; IT tools; risk management; digital technologies; team communication; international research projects; digital exclusion